STRATEGI DAN BENTUK MANAJEMEN BIAYA SEBAGAI UPAYA SUSTAINABLE KEDAI KOPI PADA MASA PANDEMI COVID-19 - Yogi Hady Afrizal; Andi Tenri Pada; Fatikah Indriaharti (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to find out how the cost management strategy is in an effort to sustain coffee shops in Ajatappareng during the Covid-19 pandemic and how the cost management forms for coffee shops in Ajatapparengduring the Covid-19 pandemic. The research method used in this study is a qualitative descriptive approach. The location of this research was carried out in the Ajatappareng area, namely the City of Pare-Pare, Kab. Pinrang and Kab. Sidrap. The results of the study show that each coffee shop has its own way or strategy in reducing costs during the pandemic in order to maintain business. Even though they have different strategies, the main goal of this strategy is to survive after the pandemic and then reorganize businesses that have been stuck due to the Covid 19 pandemic. This study implies that many businesses have gone out of business during the pandemic due to the absence of a strategy in face conditions. Keyword: Management Strategy, Cost Management and Coffee Shop